Virus-like-inspired nanoparticles facilitate bacterial internalization for enhanced eradication of drug-resistant pathogens. (12th July 2022) - Zhang, Yufei; Cheng, Yijie; Yu, Yunjian; Li, Jie; Hu, Yuqing; Gao, Yingchao; Huang, Siyuan; Wang, Wenbo; Zhang, Xinge
Abstract : The virus-like nanoplatforms promote fast bacterial adhesion, absorption, and high photothermal and reactive oxygen species utilization to eliminate bacteria and reduce the antibiotic use to avoid drug resistance and toxic side effects to organisms. Abstract : The emergence and rapid spread of bacterial resistance pose an extremely serious threat to treating infections. Inspired by the important role the spiny surface structure of a virus plays in mediating virus invasion, a spiny nanoplatform was designed and developed to eliminate drug-resistant pathogens. This biomimetic spiky surface structure increased not only the capture and internalization of bacteria but also the efficiency of light-to-heat conversion (∼36.27%), which facilitates bacterial elimination with an efficiency of around 100%. Notably, the spiny structure and surface chemical modification of the nanoplatform have a synergistic effect on the capture and phagocytosis of bacteria, which protect host cells from bacteria-triggered damage. The biomimetic nanoplatform possesses excellent biocompatibility and could also effectively disperse biofilm. Overall, the designed virus-like nanoplatform provides a reliable tool for the development of a new generation of biomimetic antibacterial agents and shows excellent prospects in fighting bacterial infection.